Diagnóstico de la situación de las PYMES de Occidente y la efectividad de los programas de apoyo. - Chacón Espeleta., Rocío (2012)
This study provides an analysis of small- and medium-sized businesses of the western region of Costa Rica. Additionally, it evaluates the effectiveness of national support programs before those businesses experienced increased globalization. The study was conducted for a period of two years, between August of 2003 and August of 2005. Data was obtained from a census of all registered businesses from all industries in the regions of Palmares, San Ramon, Grecia, Naranjo, and Valverde Vega, all of which are located in the province of Alajuela.